The Construction of Knowledge in Islamic Civilization: Qudama b. Ja 'far and His Kitab al-Kharaj wa-Sina'at al-Kitabah by Paul L. Heck (Leiden: E. J Brill, 2002. 243 pages.) (American Journal of Islam and Society, 2003)
Through the lens of genre, Heck examines Kitab al-Kharaj wa Sina 'at a/Kitabah("The Book of the Land-Tax and the Craft of Writing/Secretaryship"), a work on Islamic administration composed in Baghdadin the early fourth/tenth century by the prominent secretary Qudamah ibnJa'far (d. 337/948). His analysis ofQudamah's manual, which belongs toa body of texts that emerged in the late third/ninth century and focused primarilyon the concerns of state officials, proceeds by breaking it into constituentparts and considering each one individually in relation to earlierand contemporary works in related genres. The result is a detailed appreciationfor the work's characteristics and relative merits; showing how oneauthor constructed human knowledge; how he articulated the relationshipbetween knowledge, religion, and the 'Abbasid state; and how this por trayaldiffered from other contemporary schemes.The organization of the original work was as follows: I. Introduction,2. The Art of Writing, 3. Language and Rhetoric, 4. Bureaus of theImperial Administration, 5. Bureaus of the Imperial Administration, 6.Geography, 7. Fiscal Law, and 8. Political Thought. Unfortunately, onlychapters 5-8 survive. The unique manuscript at Istanbul's Koprulu Librarywas published in facsimile edition in 1968 and edited in 1981 (the 1981edition, Heck reports, contains numerous errors). The author's discussionuses the rubrics of language in chapter 2 (parts 2-5), geography in chapter ...